Disclosure Of Criminal Acts Of Fraud Using Social Engineering Mode Committed By Subdit V Cyber Directorate of Special Criminal Investigation South Sumatera Regional Police - Fitriyanti, Fitriyanti; Yusuf, Hambali (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
In the current era of globalization, technological progress is progressing very rapidly. We can find out information about events in other parts of the world just by accessing news via the Internet. The research method used is an empirical juridical method. What the author studied was the obstacles faced by Sub-Directorate V Cyber Ditres Crimsus Polda South Sumatra in uncovering criminal acts of fraud using social engineering. Results: From the explanation above, it is clear that crime is influenced by the social conditions of society, which can indirectly cause or encourage crime.